Ta có: [tex]\lim_{x \to 0}\frac{e^{x^2}-\cos ^{\sqrt{2}}x}{x^2}=\lim_{x \to 0}(\frac{e^{x^2}-1}{x^2}+\frac{1-\cos^{\sqrt{2}}x}{x^2})=\lim_{x \to 0}(\frac{e^{x^2}-1}{x^2}+\frac{1-\cos x}{x^2}.\frac{1-\cos^{\sqrt{2}}x}{1-\cos x})[/tex]
Ta thấy: [TEX]\lim_{x \to 0}(\frac{e^{x^2}-1}{x^2}=1[/TEX]
[TEX]\lim_{x \to 0} \frac{1-\cos x}{x^2}=\lim_{x \to 0}\frac{2\sin ^2\frac{x}{2}}{x^2}=\lim_{x \to 0}\frac{1}{2}.(\frac{\sin \frac{x}{2}}{\frac{x}{2}})^2=\frac{1}{2}[/TEX]
Đặt [TEX]\cos x=e^t[/TEX] thì ta có: [TEX]\lim _{x \to 0}\frac{1-\cos^{\sqrt{2}}x}{1-\cos x}=\lim _{t \to 0} \frac{1-e^{\sqrt{2}t}}{1-e^t}=\lim _{t \to 0} \sqrt{2}(\frac{1-e^{\sqrt{2}t}}{\sqrt{2}t}.\frac{t}{1-e^t})=\sqrt{2}[/TEX]
Từ đó [TEX]\lim_{x \to 0}\frac{e^{x^2}-\cos ^{\sqrt{2}}x}{x^2}=1+\sqrt{2}.\frac{1}{2}=1+\frac{\sqrt{2}}{2}[/TEX]
Nếu có thắc mắc gì thì bạn có thể hỏi tại đây, chúng mình luôn sẵn sàng giúp đỡ.
Chúc bạn học tốt.